2007
DOI: 10.1149/1.2374949
|View full text |Cite
|
Sign up to set email alerts
|

Co-Doped Co[sub x]Cu[sub 6−x]Sn[sub 5] Alloys as Negative Electrode Materials for Rechargeable Lithium Batteries

Abstract: A series of Co-doped Co x Cu 6−x Sn 5 ͑0 ഛ x ഛ 2͒ alloys were prepared by mechanical alloying, followed by annealing at 400°C. The Co-doped alloys show the same structure as the Cu 6 Sn 5 , which can be indexed to a hexagonal NiAs-type cell, but differ in the electrochemical performance as the anodes of Li-ion batteries. The results of ex situ X-ray diffraction analysis indicate the different Li alloying mechanism among Co x Cu 6−x Sn 5 . The metastable intermediate phases of Li 2 Co y Cu 1−y Sn formed during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Synthesis of Cu 6 Sn 5 was described elsewhere [25]. The compound was characterized by powder X-ray diffractometer (Bruker Advance8) with Cu Ka radiation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis of Cu 6 Sn 5 was described elsewhere [25]. The compound was characterized by powder X-ray diffractometer (Bruker Advance8) with Cu Ka radiation.…”
Section: Methodsmentioning
confidence: 99%
“…However, few works in the study of lithium diffusion in alloys has been reported. In our previous work, we studied the Cu 6 Sn 5 and its Co and Ni substituted alloys as lithium batteries anodes [25,26], and the relationship between the structural properties and the electrochemical performance was discussed using the experiments as well as the first-principles calculations. Following the previous studies, the goal of this paper is to investigate the kinetics of the intercalation of lithium into the Cu 6 Sn 5 alloys using both PITT and EIS method.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the Sn is also the main electrochemical active component for lithium storage . The third element (M′), such as Sb, Zn, Co,, and B could be both active and inactive for lithium storage. For example, the Sb is lithium‐active, which can alloy with lithium to form the Li 3 Sb in the alloying process, deriving a theoretical capacity of 660 mAh g −1 .…”
Section: Structures Lithiation Mechanism and Electrochemical Performentioning
confidence: 99%
“…It is due to displaying higher reversible specific capacities than carbon and the higher safety against the formation of lithium metal dendrites. Especially, tin-based metal alloys due to their low cost and high energy densities are the most exploited of alternative anode materials in lithium-ion batteries [10][11][12][13][14][15][16][17][18][19]. While tin metals can give high initial lithium insertion capacities, corresponding to a theoretical capacity of 990 mAh g −1 .…”
Section: Introductionmentioning
confidence: 99%